Fugue, Hip Hop and Soap Opera: Transcultural Connections and Theatrical Experimentation in Twenty-First Century US Latina Playwriting - García-Romero, Anne (Latin American Theatre Review, 2010)
This article examines theatrical experimentation in three plays by U.S. Latina playwrights: Quiara Alegría Hudes’ Elliot, A Soldier’s Fugue (2007), Caridad Svich’s Tropic of X (2009) and Cusi Cram’s Fuente (2009). Each playwright engages with an existing artistic form, fugue, hip hop and soap opera, as a means to develop the structure, characters and language of her play. The article argues that these playwrights’ innovations, created byexploring and subverting diverse artistic models, reflect the dynamics of transculturation and that the resulting plays are not only commercially viable but vital to twenty-first century U.S.theater. (AGR, Article in English)